2020
DOI: 10.26444/aaem/112579
|View full text |Cite
|
Sign up to set email alerts
|

Seeking genetic determinants of selected metabolic disorders in women aged 45–60

Abstract: Introduction and objective. The biochemical and anthropometric consequences of metabolic disorders exert an enormous effect on the functioning of people worldwide. The aim of this study is to assess relationships between biochemical and anthropometric parameters associated with metabolic syndrome, and the presence of the PPAR-γ rs1801282, the FTO rs9939609, and the MC4R rs17782313 polymorphisms in women aged 45-60. Materials and method. The study included 425 women, aged 45-59 years, from the general populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
2
2
0
Order By: Relevance
“…In this regard, our results show that for each risk allele (A), there is a significant increase in the amount of fatty tissue and abdominal obesity measured by WC. Its relation with the impairment of lipid metabolism, especially in TG and HDL-C, has also been suggested [48,49], which has been observed in our results. On the other hand, it has been evidenced that being a carrier of the risk allele of the rs9939609 SNP is associated with an alteration of glucose metabolism [54,58], which could be a precursor of changes in the regular brain control of adiposity and, therefore, derive in MetS [59].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In this regard, our results show that for each risk allele (A), there is a significant increase in the amount of fatty tissue and abdominal obesity measured by WC. Its relation with the impairment of lipid metabolism, especially in TG and HDL-C, has also been suggested [48,49], which has been observed in our results. On the other hand, it has been evidenced that being a carrier of the risk allele of the rs9939609 SNP is associated with an alteration of glucose metabolism [54,58], which could be a precursor of changes in the regular brain control of adiposity and, therefore, derive in MetS [59].…”
Section: Discussionsupporting
confidence: 87%
“…Although the association found between the rs9939609 SNP and MetS is in line with evidence from other authors, and remains constant in different ethnicities [47][48][49][50][51][52][53], the mechanism by which the polymorphism influences the development of MetS and the alteration of its components is unclear [47,48,54]. One hypothesis is that its role in lipogenesis, widely described [55,56], derives from the associated metabolic alterations, but this has not been demonstrated [47,57].…”
Section: Discussionsupporting
confidence: 77%
“…However, there are many inconsistencies and contradictions in the published data on these two polymorphic sites and metabolic abnormalities. Some researchers reported that C allele of the rs17782313 polymorphism is correlated with a higher level of body mass index (BMI) (38)(39)(40)(41)(42)(43), waist circumference (WC) (40,44), waist-to-hip ratio (WHR) (23), glucose (GLU) (16)(17)(18), insulin (INS) (14), triglyceride (TG) (19-21), total cholesterol (TC) (21) or low-density lipoprotein cholesterol (LDL-C) (21), and a lower level of high-density lipoprotein cholesterol (HDL-C) (45), while the experimental data obtained by other investigators could not support these conclusions (46)(47)(48)(49)(50)(51)(52)(53). There were also lots of disagreements on the relations between the PGC1a rs8192678 variant and the indexes of obesity, glucometabolic disorder and dyslipidemia.…”
Section: Introductionmentioning
confidence: 99%
“…Scientific reports of the associations between the rs1801282 and rs3856806 polymorphisms and obesity indexes as well as serum lipid levels were inconsistent and even conflicting ( 2 ). Some studies indicated that the G allele of the rs1801282 polymorphism was associated with higher levels of body mass index (BMI) ( 6 – 17 ), waist circumference (WC) ( 17 – 20 ), waist-to-hip ratio (WHR) ( 14 18 ), total cholesterol (TC) ( 21 27 ), low-density lipoprotein cholesterol (LDL-C) ( 24 – 29 ) and triglycerides (TG) ( 30 38 ), and lower levels of high-density lipoprotein cholesterol (HDL-C) ( 38 41 ), whereas the research data from other laboratories did not support these findings and even yielded contradictory results ( 42 61 ). There were also significant inconsistencies amongst published data in the relationships between the rs3856806 polymorphism and obesity indexes as well as serum lipid levels in various populations ( 62 71 ).…”
Section: Introductionmentioning
confidence: 99%